2012
DOI: 10.1016/j.matchemphys.2011.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Replication of polypyrrole with photonic structures from butterfly wings as biosensor

Abstract: Polypyrrole (PPy) with photonic crystal structures were synthesized from Morpho butterfly wings using a two-step templating process. In the first step photonic crystal SiO2 butterfly wings were synthesized from Morpho butterfly wings and in the second step the SiO2 butterfly wings were used as templates for the replication of PPy butterfly wings using an in situ polymerization method. The SiO2 templates were then removed from the PPy butterfly wings using a HF solution. The hierarchical structures down to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Photonic crystals (PCs) have recently been studied extensively because of their photonic band gaps and the unique ways of controlling the propagation of light. , In addition, photonic crystals also possess unique structural properties and interesting optical properties, such as large surface area, multiple scattering, and slow photon (SP) effect, which has been widely used in the field of reflective polarizers, sensors, solar cells, and photocatalysis . For photonic crystals photocatalyst, one of the most intriguing properties for periodic photonic structures is the high surface/volume fractions and interconnected pores, which facilitates mass transport and light harvesting. , Cai et al prepared the TiO 2 inverse opals, which showed the enhanced activity in benzoic acid photodegradation as a results of the increased path length of light within the catalysts and the large specific surface areas .…”
Section: Introductionmentioning
confidence: 99%
“…Photonic crystals (PCs) have recently been studied extensively because of their photonic band gaps and the unique ways of controlling the propagation of light. , In addition, photonic crystals also possess unique structural properties and interesting optical properties, such as large surface area, multiple scattering, and slow photon (SP) effect, which has been widely used in the field of reflective polarizers, sensors, solar cells, and photocatalysis . For photonic crystals photocatalyst, one of the most intriguing properties for periodic photonic structures is the high surface/volume fractions and interconnected pores, which facilitates mass transport and light harvesting. , Cai et al prepared the TiO 2 inverse opals, which showed the enhanced activity in benzoic acid photodegradation as a results of the increased path length of light within the catalysts and the large specific surface areas .…”
Section: Introductionmentioning
confidence: 99%
“…The second step was unique, compared to previous studies [24,52,61], and was intended to conduct a direct, fast, simple, and suitable negative imprint of the upper-wing surface of a Morpho peleides containing the veins of the wing piece, the upper laminae of the numerous cover scales, and the transition spaces between. The mounted specimen was treated with Pioloform powder (Polyvinyl Butyral, Plano GmbH, Germany) dissolved in chloroform (Sigma-Aldrich, St. Louis, USA).…”
Section: Materials and Replication Techniquementioning
confidence: 99%
“…For industrial use low-tech/high-yield solutions are of interest since they lower costs and simplify production. However, currently only soft lithography methods applied in combination with electroforming or further methods offer possibilities for industrial use [10,20,21,41,42,47,52,[56][57][58]. There has been extensive research on the use of the soft lithography method as a mass stamping tool [8, 9, 22-24, 28, 40, 41, 47, 60].…”
Section: Introductionmentioning
confidence: 99%
“…The photonic structures of the colorful butterfly wing scales have been fabricated using soft lithography technique [31], low-temperature atomic layer deposition [32,33], colloidal self-assembly, sputtering and atomic layer deposition, even combining all these layer deposition techniques together [34]. Not only sorts of surface processing technology but also a variety of materials were employed to fabricate replicas of the multi-layered scales on the surface of butterfly wing, such as polyelectrolyte multilayer films [35], carbon nanotube [36], polypyrrole [37], oxidizing material include SiO 2 [38], Bi 2 WO 6 [39], Fe 3 O 4 [40], SnO 2 [41] and so on. In addition, some works were also focused on metallic replicas [42,43] and polymer replicas [44,45].…”
Section: Introductionmentioning
confidence: 99%